Robust, defensible, and fair: the AMEE guide to selection into medical school: AMEE Guide No. 153 - Cleland, Jennifer (2023)
Selection is the first assessment of medical education and training. Medical schools must select from a pool of academically successful applicants and ensure that the way in which they choose future clinicians is robust, defensible, fair to all who apply and cost-effective. However, there is no comprehensive and evidence-informed guide to help those tasked with setting up or rejuvenating their local selection process. To address this gap, our guide draws on the latest research, international case studies and consideration of common dilemmas to provide practical guidance for designing, implementing and evaluating an effective medical school selection system. We draw on a model from the field of instructional design to frame the many different activities involved in doing so: the ADDIE model. ADDIE provides a systematic framework of Analysis (of the outcomes to be achieved by the selection process, and the barriers and facilitators to achieving these), Design (what tools and content are needed so the goals of selection are achieved), Development (what materials and resources are needed and available), Implementation (plan [including piloting], do study and adjust) and Evaluation (quality assurance is embedded throughout but the last step involves extensive evaluation of the entire process and its outcomes).